Method and system for preparing an electrospun composite membrane
Patent Information
- Application Number
- CN202510439684.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-16
AI Technical Summary
惟,使用一般熔喷法、涂布法、点贴法等方式形成贴合膜,经热压后,贴合膜覆盖在基布表面,易造成整体复合布料的透气性不足
[0027] This disclosure provides a one-stop method and system for preparing electrospun composite films, enabling the film to be prepared entirely within a single process system, eliminating the need for separate processing at other locations, thus saving transportation time and costs. Furthermore, the electrospun composite film preparation process is typically carried out at temperatures above room temperature. If a multi-station system is used, the base fabric undergoes heating at each station. However, in the one-stop system provided by this disclosure, the base fabric can be maintained at a temperature above room temperature, eliminating the need for multiple heating processes and saving energy. Moreover, this disclosure uses electrospinning technology to form the adhesive fiber layer, ensuring that both the adhesive fiber layer and the functional fiber layer on the base fabric are breathable, thus maintaining the overall breathability of the electrospun composite film while reducing process costs.
Smart Images

Figure CN122914642A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of electrospinning technology, and in particular to a one-stop continuous process method for preparing electrospun composite films. Background Technology
[0002] Electrospinning is a technique that uses a high-voltage electrostatic field to extract extremely fine fibers from a solution, thereby preparing polymer nanofibers. These fibers are commonly used in the textile industry. For example, CN104532482A utilizes needle-free electrospinning technology to produce polymer nanofibers on a large scale, rapidly, and continuously, providing single-layer electrospun nanofiber nonwoven fabrics.
[0003] This electrospinning technology can also be used to prepare composite fabrics, such as TW202428958A. It first forms an electrospun film on the surface of a meltblown adhesive film through an electrospinning process, and then directly heat-presses this meltblown adhesive film with the electrospun film onto the surface of the base fabric, thereby forming a composite fabric. However, when using conventional meltblowing, coating, or dot-bonding methods to form the laminating film, after heat pressing, the laminating film covers the surface of the base fabric, which can easily lead to insufficient breathability of the overall composite fabric.
[0004] Moreover, the current technology for preparing composite fabrics through electrospinning usually involves multi-station processes. For example, the process of making the electrospun film and the process of bonding the electrospun film to the base fabric are carried out in different factories or process systems, which results in the waste of time and raw materials, and makes it impossible to reduce the overall process cost. Summary of the Invention
[0005] The purpose of this disclosure is to provide a method for preparing electrospun composite membranes in a one-stop process. By using a continuous conveyor belt to form an adhesive layer and a functional fiber layer on a base fabric through electrospinning technology, the overall air permeability of the electrospun composite membrane can be maintained, and the process cost can be reduced.
[0006] This disclosure provides a method for preparing an electrospun composite film, comprising:
[0007] The first base fabric is fixed to a conveying device;
[0008] Driven by the conveying device, the first base fabric is passed through the first electrospinning device to form a first adhesive fiber layer on one surface of the first base fabric;
[0009] A first base fabric having the first adhesive fiber layer is driven by the conveying device and passed through a second electrospinning device to form a first functional fiber layer on the first adhesive fiber layer of the first base fabric; and
[0010] The first base fabric having the first adhesive fiber layer and the first functional fiber layer is driven by the conveying device and passed through a hot press to form the electrospun composite film after hot pressing.
[0011] In this disclosure, before the first base fabric having the first adhesive fiber layer and the first functional fiber layer passes through the hot press, the preparation method further includes passing the first base fabric having the first adhesive fiber layer and the first functional fiber layer through a hot oven driven by the conveying device; passing the first base fabric having the first adhesive fiber layer and the first functional fiber layer through a third electrospinning device driven by the conveying device to form a second adhesive fiber layer on the first functional fiber layer; and applying the second base fabric to the second adhesive fiber layer and passing it through the hot press to form the electrospun composite film.
[0012] This disclosure also provides a system for preparing electrospun composite films, comprising:
[0013] A conveying device, comprising an input end and an output end;
[0014] A first electrospinning device is disposed between the input end and the output end of the conveying device, and includes an adhesive receiving component.
[0015] A second electrospinning device, disposed between the output end of the first electrospinning device and the conveying device, includes a functional solution-containing component; and
[0016] A hot press is disposed between the output end of the second electrospinning device and the conveying device.
[0017] In this disclosure, the system for preparing electrospun composite films further includes a hot oven, a third electrospinning device, and a fabric input device, wherein the hot oven is disposed between the second electrospinning device and the hot press; the third electrospinning device is disposed between the hot oven and the hot press; and the fabric input device is disposed between the third electrospinning device and the hot press.
[0018] In this disclosure, the temperature of the hot oven is higher than the melting point of the material of the first adhesive fiber layer and lower than the melting point of the material of the first functional fiber layer.
[0019] In this disclosure, the temperature of the hot oven is from about 60°C to about 200°C.
[0020] In this disclosure, the temperature of the hot press is higher than the melting point of the material of the first adhesive fiber layer and lower than the melting point of the material of the first functional fiber layer.
[0021] In this disclosure, the hot pressing temperature of the hot press is from about 80°C to about 300°C.
[0022] In this disclosure, the first electrospinning device, the second electrospinning device, and the third electrospinning device are needleless electrospinning devices.
[0023] In this disclosure, the average fiber fineness of the first adhesive fiber layer and the second adhesive fiber layer is equal to or greater than the average fiber fineness of the first functional fiber layer; and the basis weight of the first adhesive fiber layer and the second adhesive fiber layer is equal to or less than the basis weight of the first functional fiber layer.
[0024] In this disclosure, each of the first and second adhesive fiber layers has an average fiber fineness of about 200 nm to about 700 nm and a weight per square meter (g / M). 2 (approximately 20g / M) 2 The base weight.
[0025] In this disclosure, the first functional fiber layer has an average fiber fineness of about 80 nm to about 500 nm and about 1 g / M 2 Approximately 20g / M 2 The base weight.
[0026] In this disclosure, the first functional fiber layer includes one or more additives selected from water-repellent agents, antibacterial agents, deodorizing agents, anti-mite agents, and colorants.
[0027] This disclosure provides a one-stop method and system for preparing electrospun composite films, enabling the film to be prepared entirely within a single process system, eliminating the need for separate processing at other locations, thus saving transportation time and costs. Furthermore, the electrospun composite film preparation process is typically carried out at temperatures above room temperature. If a multi-station system is used, the base fabric undergoes heating at each station. However, in the one-stop system provided by this disclosure, the base fabric can be maintained at a temperature above room temperature, eliminating the need for multiple heating processes and saving energy. Moreover, this disclosure uses electrospinning technology to form the adhesive fiber layer, ensuring that both the adhesive fiber layer and the functional fiber layer on the base fabric are breathable, thus maintaining the overall breathability of the electrospun composite film while reducing process costs. Attached Figure Description
[0028] Figure 1 This is a schematic diagram of an embodiment of the system used in this disclosure for preparing electrospun composite films.
[0029] Figure 2 This is a three-dimensional schematic diagram of an embodiment of the electrospun composite membrane disclosed herein.
[0030] Figure 3This is a schematic diagram of another embodiment of the system used in this disclosure for preparing electrospun composite films.
[0031] Figure 4 This is a three-dimensional schematic diagram of another embodiment of the electrospun composite membrane disclosed herein.
[0032] Figure 5 A scanning electron microscope (SEM) image (magnification 2,500x) of the first adhesive fiber layer of the electrospun composite membrane disclosed herein.
[0033] Figure 6 A scanning electron microscope (SEM) image (10,000x magnification) of the first adhesive fiber layer of the electrospun composite film disclosed herein.
[0034] Figure 7 A scanning electron microscope (SEM) image (magnification 2,500x) of the first functional layer of the electrospun composite film disclosed herein.
[0035] Figure 8 The image is a scanning electron microscope (SEM) image (magnification 2,500x) of the electrospun composite film disclosed in this paper. Detailed Implementation
[0036] This disclosure will be more readily understood by referring to this detailed description and the examples included herein. Several specific details are set forth to provide a thorough understanding of the examples described herein. However, those skilled in the art will understand that the examples described herein can be practiced without such specific details. Furthermore, the description herein is not intended to limit the scope of this disclosure.
[0037] Unless otherwise stated herein, the terms “a,” “the,” and similar expressions used in this specification (especially in the claims described below) shall be understood to include both singular and plural forms. Furthermore, for clarity, the dimensions of components and areas may be exaggerated in the drawings and not drawn to scale.
[0038] It should be understood that any numerical range referenced in this specification is intended to include all subranges encompassed therein. For example, a range from "1 to 10" includes all subranges (such as from 2 to 8, 3 to 6, or 4 to 9, etc.) between the stated minimum value of 1 and the stated maximum value of 10, and includes both values; that is, it includes a range of minimum values equal to or greater than 1 and maximum values equal to or less than 10. Because the disclosed numerical ranges are continuous, they include every value between the minimum and maximum values. Unless otherwise stated, the various numerical ranges specified in this specification are approximate values.
[0039] Furthermore, in this paper, all numerical values are assumed to be modified by the term "approximately," which means the numerical variation as expected by those skilled in the art in terms of the accuracy of the measurement and operation and the measuring equipment used.
[0040] Please refer to Figure 1 As shown, this disclosure describes a system for preparing electrospun composite films, comprising:
[0041] The conveying device 10 includes an input end 11 with a first base fabric roll and an output end 12 with a take-up roller. One or more support rollers 13 may be provided between the input end 11 and the output end 12 as needed. The conveying device 10 can be driven by a motor. The first base fabric roll receives the first base fabric 91 to be processed and inputs the first base fabric 91 into the system. The take-up roller 12 can take up the processed first base fabric 91.
[0042] The first electrospinning device 20 is disposed between the input end 11 and the output end 12 of the conveying device 10. It includes an adhesive receiving component 21 and a plurality of nozzles 22 communicating with the adhesive receiving component 21. The adhesive receiving component 21 contains an adhesive solution, so that when the first electrospinning device 20 is in operation, the adhesive can be sprayed from the nozzles 22 toward the first base fabric 91.
[0043] The second electrospinning device 30, disposed between the first electrospinning device 20 and the output end 12 of the conveying device 10, includes a functional solution receiving component 31 and a plurality of nozzles 32 communicating with the functional solution receiving component 31. The functional solution receiving component 31 contains a functional solution, so that when the second electrospinning device 30 is in operation, the functional solution can be ejected from the nozzles 32 toward the first base fabric 91; and
[0044] A hot press 70 is disposed between the second electrospinning device 31 and the output end 12 of the conveying device 10. The hot press 70 includes at least one set of hot press rollers 71 connected vertically, so that the first base fabric 91 can pass between the hot press rollers 71 when the hot press 70 is in operation.
[0045] This disclosure can be used in conjunction with the above-described system for preparing electrospun composite films to provide a method for preparing electrospun composite films. Therefore, the following method is used in conjunction with... Figure 1 While this disclosure provides an explanation, the method for preparing electrospun composite films is not limited to the system described above for preparing electrospun composite films. As long as it conforms to the spirit and scope of the method disclosed herein, it shall still fall within the scope of protection of this disclosure. Therefore, the scope of protection of this disclosure shall be determined by the appended claims.
[0046] Please refer to Figure 1 and Figure 2The method for preparing the electrospun composite film disclosed herein includes:
[0047] The first base fabric 91 is fixed to the conveying device 10, and the first base fabric 91 travels from the first base fabric roll at the input end 11 to the take-up roller at the output end 12 (e.g., Figure 1 (As indicated by the arrow);
[0048] Driven by the conveying device 10, the first base fabric 91 is spun by the first electrospinning device 20 to form a first adhesive fiber layer 92 on one surface of the first base fabric 91.
[0049] Having the first adhesive fiber layer 92 ( Figure 1 The first base fabric 91 (not shown) is driven by the conveying device 10 and passed through the second electrospinning device 30 to form a first functional fiber layer 93 on the first adhesive fiber layer 92 of the first base fabric 91. Figure 1 (Not shown in the text); and
[0050] A first base fabric 91 having the first adhesive fiber layer 92 and the first functional fiber layer 93 is driven by the conveying device 10 and passed through a hot press 70 to form the electrospun composite film 90 after hot pressing. Figure 2 As shown, the electrospun composite film 90 may have a three-layer structure, including a first base fabric 91, a first adhesive fiber layer 92 and a first functional fiber layer 93, wherein the first base fabric 91 and the first functional fiber layer 93 are bonded together via the first adhesive fiber layer 92.
[0051] The first base fabric 91 may be an outer fabric, which may be woven or nonwoven, and its material may include, but is not limited to: polyester, nylon, polypropylene, polyvinylpyrrolidone or combinations thereof.
[0052] [First electrospinning apparatus]
[0053] The first electrospinning device 20 can be a high-voltage electrospinning device or a needleless electrospinning device. In some embodiments, the first electrospinning device 20 can be a needleless electrospinning device, which is an open system with high spinning speed and can be used for large-scale production. Please refer to [reference needed]. Figure 1 When the first base fabric 91 passes through the first electrospinning device 20, it is positioned above the nozzle 22 of the first electrospinning device 20. The nozzle 22 of the first electrospinning device 20 sprays adhesive onto the surface of the first base fabric 91. Under a high-voltage electric field (the high-voltage power supply voltage is controlled between about 50kV and about 120kV), the solvent in the adhesive evaporates, forming a first adhesive fiber layer 92 on the first base fabric 91. This layer has an average fiber fineness of about 200nm to about 700nm and a weight per square meter (g / M). 2(approximately 20g / M) 2 The base weight.
[0054] In some embodiments, the first adhesive fiber layer 92 may have an average fiber fineness of about 300 nm to about 450 nm. In some embodiments, the first adhesive fiber layer 92 may have an average fiber fineness of about 350 nm to about 400 nm, thereby enabling the first adhesive fiber layer 92 and the final electrospun composite membrane 90 to possess good air permeability and flexibility. In some embodiments, the first adhesive fiber layer 92 may have a weight per square meter (g / M²) of about 2 g / m². 2 (approximately 15g / M) 2 The basis weight. In some embodiments, the first adhesive fiber layer 92 may have a basis weight of approximately 3 m² (g / m²). 2 (approximately 10 g / M) 2 The basis weight. By adjusting the fiber fineness of the nanofibers in the first adhesive fiber layer 92, the first adhesive fiber layer 92 can have a suitable pore size, thereby achieving both high breathability and high water resistance, and providing sufficient adhesion between the first base fabric 91 and the first functional fiber layer 93. In this disclosure, the average fiber fineness of the nanofibers in the first adhesive fiber layer 92 is from about 200 nm to about 700 nm, which allows the first adhesive fiber layer 92 to provide high water resistance while maintaining good adhesion.
[0055] Since the first base fabric 91 travels in the overall system at a certain speed, the number and density of the nozzles 22 can be adjusted in the first electrospinning device 20 according to the basis weight of the first adhesive fiber layer 92 to be obtained.
[0056] The adhesive receiving component 21 can be a tank, pipeline, or other component capable of containing and conveying the adhesive to the nozzle 22 of the first electrospinning device 20. The type of adhesive can be selected based on the types of the first base fabric 91 and the first functional fiber layer 93. In some embodiments, the materials of the first functional fiber layer 93 and the first base fabric 91 can be Nylon, and the adhesive can also be a Nylon-based adhesive, thereby giving the electrospun composite film 90 an overall material isomorphism, which is beneficial for hot pressing within a specific temperature range. Furthermore, when the materials of the first base fabric 91, the first adhesive fiber layer 92, and the first functional fiber layer 93 are all Nylon, since the first base fabric 91, the first adhesive fiber layer 92, and the first functional fiber layer 93 all melt at the interface, the structural strength (tensile strength) and interlayer strength (peel strength) of the electrospun composite film 90 disclosed herein can be further improved.
[0057] In some embodiments, the adhesive may be a nitrile adhesive, and the solvent may be an alcohol solvent, giving the adhesive advantages such as volatility, low toxicity, and low corrosivity, thus making it environmentally friendly. The concentration of the adhesive is from about 10 wt% to about 20 wt%. In some other embodiments, the adhesive may also include polyurethane (PU), polymethyl methacrylate (PMMA), polyvinyl acetate (PVAC), etc., wherein polymethyl methacrylate may use dimethylacetamide (DMAc) as a solvent, and polyvinyl acetate may use water as a solvent.
[0058] [Second electrospinning device]
[0059] The second electrospinning device 30 can be a high-voltage electrospinning device or a needleless electrospinning device. In some embodiments, the second electrospinning device 30 can be a needleless electrospinning device. Please refer to... Figure 1 When the first base fabric 91 having a first adhesive fiber layer 92 passes through the second electrospinning device 30, it is positioned above the nozzle 32 of the second electrospinning device 30. The nozzle 32 of the second electrospinning device 30 sprays a functional solution onto the first adhesive fiber layer 92 of the first base fabric 91. Through a high-voltage electric field (the high-voltage power supply voltage is controlled between approximately 50kV and approximately 120kV), the solvent in the functional solution evaporates, forming a first functional fiber layer 93 on the first adhesive fiber layer 92 of the first base fabric 91. This functional fiber layer 93 has an average fiber fineness of approximately 80nm to approximately 500nm and a weight per square meter (g / M²). 2 (approximately 20g / M) 2 The base weight.
[0060] In some embodiments, the first functional fiber layer 93 may have an average fiber fineness of about 100 nm to about 300 nm. In some embodiments, the first functional fiber layer 93 may have an average fiber fineness of about 150 nm to about 250 nm, thereby enabling the first functional fiber layer 93 and the final electrospun composite membrane 90 to possess good air permeability and flexibility. In some embodiments, the first functional fiber layer 93 may have a weight per square meter (g / m²) of about 2 g / m². 2 (approximately 15g / M) 2 The basis weight. In some embodiments, the first functional fiber layer 93 may have a basis weight of approximately 3 m² (g / m²). 2 (approximately 10 g / M) 2The basis weight. By adjusting the fiber fineness of the nanofibers in the first functional fiber layer 93, the first functional fiber layer 93 can have a suitable pore size, thereby achieving both high breathability and high water resistance. In this disclosure, the average fiber fineness of the first functional fiber layer 93 is from about 80 nm to about 500 nm, which enables the first functional fiber layer 93 to provide high water resistance. If the nanofibers are compressed more tightly to reduce the pore size, although this can improve water resistance, it will reduce the breathability of the first functional fiber layer 93. In some embodiments, the average pore size of the first functional fiber layer 93 is from about 0.5 μm to about 5.5 μm; in some embodiments, the average pore size of the first functional fiber layer 93 is from about 0.75 μm to about 4 μm; in some embodiments, the average pore size of the first functional fiber layer 93 is from about 0.8 μm to about 2 μm.
[0061] Since the first base fabric 91 travels in the overall system at a certain speed, the number and density of the nozzles 32 can be adjusted in the second electrospinning device 30 according to the basis weight of the first functional fiber layer 93 to be obtained.
[0062] In some embodiments, the average fiber fineness of the first functional fiber layer 93 (see [reference]). Figure 7 The electron microscope image shown may be equal to or smaller than the first adhesive fiber layer 92 (see reference). Figure 5 The average fiber fineness (as shown in the electron microscope image) is such that, in some embodiments, the ratio of the average fiber fineness of the first functional fiber layer 93 to the average fiber fineness of the first adhesive fiber layer 92 may be from about 1:1 to about 1:5; or, the ratio may be from about 1:1.5 to about 1:3. In some embodiments, the basis weight of the first functional fiber layer 93 may be equal to or greater than the basis weight of the first adhesive fiber layer 92. In some embodiments, the ratio of the basis weight of the first functional fiber layer 93 to the basis weight of the first adhesive fiber layer 92 may be from about 1:1 to about 10:1; or, the ratio may be from about 1.5:1 to about 7:1; or, the ratio may be from about 3:1 to about 5:1.
[0063] The functional solution receiving component 31 may be a tank, pipeline, or other component capable of containing and conveying the functional solution to the nozzle 32 of the second electrospinning apparatus 30. The functional solution may be selected based on the desired properties of the electrospun composite membrane 90. In some embodiments, the functional solution may be a nylon-based solution, the solvent may be an alcohol solvent, and the concentration of the functional solution may be from about 5 wt% to about 15 wt%. The functional solution may also be polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polyisopropylacrylamide, or other materials commonly used in the preparation of electrospinning. Furthermore, the functional solution may further include one or more additives to impart different properties to the first functional fiber layer 93 obtained from the functional solution, such as water-repellent agents, antibacterial agents, deodorizing agents, anti-mite agents, colorants (e.g., dyes or pigments), etc.
[0064] In some embodiments, the functional solution may further include colorants, such as dyes or pigments, to provide the first functional fiber layer 93 with a variety of color choices. By adjusting the amount of colorants (such as dyes or pigments) added, a rich visual effect of varying shades can be created, enhancing the aesthetics and application flexibility of the first functional fiber layer 93. For example, by increasing the concentration of the colorant, the color saturation that the first functional fiber layer 93 can present can range from light to dark, and both the type and concentration of the colorant can be adjusted as needed.
[0065] In some embodiments, the functional solution includes a nylon copolymer and an alcohol as a solvent. The nylon copolymer and alcohol impart good spinnability to the functional solution. Additional additives may be added to further endow the nanofibers in the first functional fiber layer 93 with high fiber strength and high fiber elongation, and to impart high hydrophobicity to the electrospun composite membrane 90. In some embodiments, the nylon copolymer may be a copolymer of a copolyamide and an alkoxy-modified nylon 46 / 66 copolymer to facilitate dissolution in alcohols, thereby improving the spinnability of the electrospinning solution.
[0066] [Hot Press]
[0067] The temperature of the hot press 70 can be higher than the melting point of the material of the first adhesive fiber layer 92 and lower than the melting point of the material of the first functional fiber layer 93. In some embodiments, the hot pressing temperature of the hot press 70 is about 80°C to about 300°C; in some embodiments, the hot pressing temperature of the hot press 70 is about 90°C to about 260°C; in some embodiments, the hot pressing temperature of the hot press 70 is about 100°C to about 200°C. During the hot pressing process, the first adhesive fiber layer 92 may partially melt between the first functional fiber layer 93 and the first base fabric 91, but the first functional fiber layer 93 remains unmelted to bond the first functional fiber layer 93 and the first base fabric 91 together. Because the first adhesive fiber layer 92 melts at its respective interfaces with the first functional fiber layer 93 and the first base fabric 91, the first adhesive fiber layer 92 penetrates into the spaces between the multiple nanofibers of the first functional fiber layer 93 at its interface with the first functional fiber layer 93. Furthermore, after melting, the first adhesive fiber layer 92 penetrates into the spaces between the multiple fibers of the first base fabric 91 from its interface with the first base fabric 91, thereby forming a tight and strong adhesion to obtain the electrospun composite film 90 (see [reference]). Figure 8 (Electron microscope image).
[0068] The hot press 70 includes at least one set of hot press rollers 71 connected vertically. The hot press rollers 71 can be embossing rollers (i.e., patterned roller application method) or smooth rollers (i.e., smooth roller application method). In some embodiments, the roller speed of the hot press rollers 71 can be from about 0.1 m / min to about 10 m / min; in some embodiments, the roller speed of the hot press rollers 71 can be from about 0.5 m / min to about 6 m / min; in some embodiments, the roller speed of the hot press rollers 71 can be from about 1 m / min to about 3.5 m / min.
[0069] The system disclosed herein for preparing electrospun composite films may be further comprised of various different devices depending on the desired properties of the electrospun composite film.
[0070] like Figure 3 and Figure 4 As shown, the system disclosed herein for preparing electrospun composite films may include the conveying device 10, the first electrospinning device 20, the second electrospinning device 30, and the hot press 70 as described above, and therefore will not be described in detail here. The system further includes:
[0071] A hot drying oven 40 is disposed between the second electrospinning device 30 and the hot press 70. It may have a plurality of transfer rollers 41. Since the first base fabric 91 moves in the overall system at a certain speed, the time the first base fabric 91 passes through the hot drying oven 40 can be controlled by the number and position configuration of the transfer rollers 41, so as to ensure that the first adhesive fiber layer 92 is melted and penetrates into the first base fabric 91 and the first functional fiber layer 93 to ensure the bonding effect.
[0072] A third electrospinning apparatus 50, disposed between the hot oven 40 and the hot press 70, includes an adhesive receiving component 51 and a plurality of nozzles 52 communicating with the adhesive receiving component 51. The adhesive receiving component 51 contains an adhesive solution, allowing the adhesive to be sprayed from the nozzles 52 toward the first base fabric 91 during operation of the third electrospinning apparatus 50. The adhesive in the third electrospinning apparatus 50 may be the same as or different from the adhesive in the first electrospinning apparatus 20, and the adhesive in the third electrospinning apparatus 50 may be selected according to the type of the first functional fiber layer 93 and the subsequently provided second base fabric 95; and
[0073] The fabric input device 60 is located between the third electrospinning device 50 and the hot press 70. It is used to input the second base fabric 95 into the system and press it into the hot press 70 in parallel with the first base fabric 91 and its layers.
[0074] like Figure 3 and Figure 4 As shown, the method for preparing the electrospun composite film disclosed herein, after forming the first adhesive fiber layer 92 and the first functional fiber layer 93 on the surface of the first base fabric 91 and before passing it through a hot press, further includes:
[0075] A first base fabric 91 having a first adhesive fiber layer 92 and a first functional fiber layer 93 is driven by the conveying device 10 through a hot drying oven 40. The hot drying oven 40 has a plurality of transfer rollers 41. The time for the first base fabric 91 to pass through the hot drying oven 40 is controlled by adjusting the number and position of these transfer rollers 41. The temperature of the hot drying oven 40 is higher than the melting point of the material of the first adhesive fiber layer 92 and lower than the melting point of the material of the first functional fiber layer 93. For example, the temperature of the hot drying oven may be about 60°C to about 200°C; in some embodiments, the temperature of the hot drying oven is about 80°C to about 180°C; in some embodiments, the temperature of the hot drying oven is about 100°C to about 150°C.
[0076] A first base fabric 91 having the first adhesive fiber layer 92 and the first functional fiber layer 93 is driven by the conveying device 10 and passed through the third electrospinning device 50 to form a second adhesive fiber layer 94 on the first functional fiber layer 93. Figure 3 (Not shown in the image), the components and configuration (including the adhesive formulation) of the third electrospinning apparatus 50 may be substantially the same as those of the first electrospinning apparatus 20, and may also be adjusted as needed; and
[0077] The second base fabric 95 is applied to the second adhesive fiber layer 94, and the electrospun composite film 90 is formed by passing it through the hot press 70. Figure 4As shown, the electrospun composite film 90 may have a five-layer structure, including a first base fabric 91, a first adhesive fiber layer 92, a first functional fiber layer 93, a second adhesive fiber layer 94, and a second base fabric 95, wherein the first base fabric 91 and the first functional fiber layer 93 are bonded together via the first adhesive fiber layer 92, and the second base fabric 95 and the first functional fiber layer 93 are bonded together via the second adhesive fiber layer 94.
[0078] In some embodiments, the system and method disclosed herein for preparing electrospun composite films may include the use of more electrospinning devices to form an electrospun composite film 90 comprising more layers, such as forming more adhesive fiber layers and / or more functional fiber layers, such as water-repellent fibers, antibacterial fibers, deodorizing fibers, anti-mite fibers, fibers in different colors, UV-resistant fibers, far-infrared fibers, etc. In some embodiments, a first base fabric pretreatment device may be provided before forming the first adhesive fiber layer 92 to pretreat any surface of the first base fabric 91. However, the embodiments disclosed above do not constitute any limitation on this disclosure.
[0079] Example
[0080] Test items and instruments
[0081] Fiber basis weight: The measurement of the weight of fabric per unit area using ASTM D3776 standard.
[0082] Average pore size: using a capillary pore tester from PMI.
[0083] Air permeability: Complies with ASTM D737 standard.
[0084] Water vapor permeability: JIS L 1099B1 standard.
[0085] Hydrostatic pressure test: Using JIS L1092-5.1-B standard, calculate the maximum number of centimeters (mm) of water column that can be withstood per square centimeter (mm) without leakage. The larger the value, the better the hydrostatic pressure resistance (waterproofing).
[0086] Peel strength: Measured using ISO 2411 standard for the coating adhesion of rubber and plastic coated textiles.
[0087] Wash resistance test: The AATCC 135-2018 standard was used to test the change in fabric size after household washing. The washing parameters were: standard mode / 20 cycles (with detergent / in a laundry bag). According to the AATCC 135-2018 washing mode, the standard mode (Normal) is 660±15RPM.
[0088] Rain test: Using the AATCC 35 standard, the principle is to spray water onto the sample surface for 5 minutes, place a weighed absorbent paper behind the sample, and then weigh the sprayed absorbent paper to determine the water permeability. In this test, the fabric is tilted at a 45° angle to simulate raindrops, and the test is conducted for 5 minutes. The operating parameters are controlled at 1 gram x 2 feet x 5 minutes (1g, 5min@3ft).
[0089] Water vapor resistance: The CNS15102L3256 standard is used for the test method of thermal resistance and water vapor resistance (sweating hot plate) of textiles under steady state for comfort.
[0090] Example 1
[0091] In Example 1, a nylon weft-stretch plain weave fabric is fixed to a conveying device, which drives a first electrospinning device controlled by a voltage of approximately 80 kV. The first electrospinning device sprays an ethanol solution containing bio-nylon (concentration of approximately 15 wt%) as an adhesive onto the nylon weft-stretch plain weave fabric to form a first adhesive fiber layer on the surface of the nylon weft-stretch plain weave fabric, which has an average fiber fineness of approximately 377 nm and a fiber density of approximately 2.5 g / m². 2 The basis weight; the nylon weft elastic plain weave fabric having the first bonded fiber layer is then driven by a conveying device through a second electrospinning device with a voltage controlled at about 80kV. The second electrospinning device sprays an ethanol solution containing bio-nylon (concentration of about 7wt%) as a functional solution onto the first bonded fiber layer to form a first functional fiber layer on the surface of the first bonded fiber layer, which has an average fiber fineness of about 276nm and a weight of about 10g / M 2 The basis weight and average pore size of approximately 0.8 μm; the Nylon weft-elastic plain weave fabric having a first adhesive fiber layer and a first functional fiber layer is then driven by a conveying device through a hot drying oven and heated to a temperature of approximately 135°C, and then passed through a third electrospinning device with a voltage controlled at approximately 80 kV. The third electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 15 wt%) as an adhesive onto the first functional fiber layer to form a second adhesive fiber layer on the surface of the Nylon weft-elastic plain weave fabric, which has an average fiber fineness of approximately 377 nm and approximately 2.5 g / M 2The basis weight; then the Nylon circular knitted fabric is applied to the second adhesive fiber layer, and then the multilayer structure is hot-pressed by a hot press at a hot press roller speed of about 1 m / min and a hot press temperature of about 100°C to obtain the electrospun composite film of Example 1.
[0092] Further performance tests were conducted on the electrospun composite membrane of Example 1, including water pressure resistance, air permeability, moisture permeability, peel strength, rain test, and wash resistance test. The results showed that the electrospun composite membrane of Example 1 had a water pressure resistance of approximately 10,000 mmH2O and a water permeability of approximately 0.7 CFM (cubic feet per minute). 3 The air permeability is approximately 20,000 g / m³. 2 *24hr moisture permeability, approximately 204g / cm peel strength, and has passed rain test (the weight difference before and after the absorbent paper test is approximately 0.1g) and wash resistance test (visually no peeling after 50 washes).
[0093] Example 2
[0094] In Example 2, Nylon fabric is fixed to a conveying device, which drives a first electrospinning device controlled by a voltage of approximately 50 kV. The first electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 7 wt%) as an adhesive onto the Nylon fabric to form a first adhesive fiber layer on the surface of the Nylon fabric, which has an average fiber fineness of approximately 200 nm and a fiber density of approximately 2 g / M. 2 The basis weight; the Nylon fabric having the first bonded fiber layer is then driven by a conveying device through a second electrospinning device with a voltage controlled at about 80kV. The second electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of about 5wt%) as a functional solution onto the first bonded fiber layer to form a first functional fiber layer on the surface of the first bonded fiber layer, which has an average fiber fineness of about 200nm and a basis weight of about 3g / M. 2 The basis weight and average pore size of approximately 1.7 μm; the Nylon fabric having a first adhesive fiber layer and a first functional fiber layer is then driven by a conveying device through a hot drying oven and heated to a temperature of approximately 60°C, and then passed through a third electrospinning device with a voltage controlled at approximately 50 kV. The third electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 7 wt%) as a binder onto the first functional fiber layer to form a second adhesive fiber layer on the surface of the Nylon fabric, which has an average fiber fineness of approximately 200 nm and a basis weight of approximately 1.8 g / m². 2 The basis weight; then another Nylon fabric is applied to the second adhesive fiber layer, and the multilayer structure is hot-pressed by a hot press at a hot press roller speed of about 6 m / min and a hot press temperature of about 80°C to obtain the electrospun composite film of Example 2.
[0095] Further performance tests were conducted on the electrospun composite membrane of Example 2, including water pressure resistance, air permeability, moisture permeability, peel strength, rain test, and wash resistance test. The results showed that the electrospun composite membrane of Example 2 had a water pressure resistance of approximately 2,000 mmH2O, an air permeability of approximately 20 CFM, and a strength of approximately 100,000 g / m³. 2 *24hr moisture permeability, approximately 207g / cm peel strength, and has passed rain test (the weight difference before and after the absorbent paper test is approximately 0.1g) and wash resistance test (visually no peeling after 50 washes).
[0096] Example 3
[0097] In Example 3, Nylon fabric is fixed to a conveying device, which drives a first electrospinning device controlled by a voltage of approximately 75 kV. The first electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 7 wt%) as an adhesive onto the Nylon fabric to form a first adhesive fiber layer on the surface of the Nylon fabric, which has an average fiber fineness of approximately 250 nm and a fiber density of approximately 2.9 g / m³. 2 The basis weight; the Nylon fabric having the first bonded fiber layer is then driven by a conveying device through a second electrospinning device with a voltage controlled at about 75kV. The second electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of about 5wt%) as a functional solution onto the first bonded fiber layer to form a first functional fiber layer on the surface of the first bonded fiber layer, which has an average fiber fineness of about 500nm and a basis weight of about 3g / M. 2 The basis weight and average pore size of approximately 5.4 μm; the Nylon fabric having a first adhesive fiber layer and a first functional fiber layer is then driven by a conveying device through a hot drying oven and heated to a temperature of approximately 110°C, and then passed through a third electrospinning device with a voltage controlled at approximately 75 kV. The third electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 7 wt%) as a binder onto the first functional fiber layer to form a second adhesive fiber layer on the surface of the Nylon fabric, which has an average fiber fineness of approximately 248 nm and a basis weight of approximately 3.03 g / m³. 2 The basis weight; then another Nylon fabric is applied to the second adhesive fiber layer, and the multilayer structure is hot-pressed by a hot press at a hot press roller speed of about 3.5 m / min and a hot press temperature of about 100°C to obtain the electrospun composite film of Example 3.
[0098] Further performance tests were conducted on the electrospun composite membrane of Example 3, including water pressure resistance, air permeability, moisture permeability, peel strength, rain test, and wash resistance test. The results showed that the electrospun composite membrane of Example 3 had a water pressure resistance of approximately 1,000 mmH2O, an air permeability of approximately 12 CFM, and a strength of approximately 120,000 g / m³. 2*24hr moisture permeability, approximately 213g / cm peel strength, and has passed rain test (the weight difference before and after the absorbent paper test is approximately 0.1g) and wash resistance test (visually no peeling after 50 washes).
[0099] Example 4
[0100] In Example 4, Nylon fabric is fixed to a conveying device, which drives a first electrospinning device controlled by a voltage of approximately 75 kV. The first electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 7 wt%) as an adhesive onto the Nylon fabric to form a first adhesive fiber layer on the surface of the Nylon fabric, which has an average fiber fineness of approximately 250 nm and a fiber density of approximately 5.2 g / m³. 2 The basis weight; the Nylon fabric having the first bonded fiber layer is then driven by a conveying device through a second electrospinning device with a voltage controlled at about 75kV. The second electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of about 7wt%) as a functional solution onto the first bonded fiber layer to form a first functional fiber layer on the surface of the first bonded fiber layer, which has an average fiber fineness of about 273nm and a basis weight of about 7g / M. 2 The basis weight and average pore size of approximately 1.08 μm; the Nylon fabric having a first adhesive fiber layer and a first functional fiber layer is then driven by a conveying device through a hot drying oven, heated to a temperature of approximately 110°C, and then passed through a third electrospinning device with a voltage controlled at approximately 75 kV. The third electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 7 wt%) as a binder onto the first functional fiber layer to form a second adhesive fiber layer on the surface of the Nylon fabric, which has an average fiber fineness of approximately 252 nm and a basis weight of approximately 5.1 g / M. 2 The basis weight; then another Nylon fabric is applied to the second adhesive fiber layer, and the multilayer structure is hot-pressed by a hot press at a hot press roller speed of about 2 m / min and a hot press temperature of about 100°C to obtain the electrospun composite film of Example 4.
[0101] Further performance tests were conducted on the electrospun composite membrane of Example 4, including water pressure resistance, air permeability, moisture permeability, peel strength, rain test, and wash resistance test. The results showed that the electrospun composite membrane of Example 4 had a water pressure resistance of approximately 5,000 mmH2O, an air permeability of approximately 3 CFM, and a strength of approximately 70,000 g / m³. 2 *24hr moisture permeability, approximately 258g / cm peel strength, and has passed rain test (the weight difference before and after the absorbent paper test is approximately 0.1g) and wash resistance test (visually no peeling after 50 washes).
[0102] Example 5
[0103] In Example 5, marine waste Nylon fabric is fixed to a conveying device, which is driven by a first electrospinning device controlled by a voltage of approximately 80 kV. The first electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 15 wt%) as an adhesive onto the marine waste Nylon fabric to form a first adhesive fiber layer on the surface of the marine waste Nylon fabric, which has an average fiber fineness of approximately 350 nm and a fiber density of approximately 5.2 g / M. 2 The basis weight; the marine waste Nylon fabric having the first bonded fiber layer is then driven by a conveying device through a second electrospinning device with a voltage controlled at about 80kV. The second electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of about 7wt%) as a functional solution onto the first bonded fiber layer to form a first functional fiber layer on the surface of the first bonded fiber layer, which has an average fiber fineness of about 302nm and a weight of about 10g / M 2 The biopolymer nylon fabric, having a basis weight and an average pore size of approximately 1.1 μm, is then conveyed by a conveying device through a hot oven and heated to approximately 120°C. It is then passed through a third electrospinning device with a voltage controlled at approximately 80 kV. The third electrospinning device sprays an ethanol solution containing biopolymer nylon (concentration approximately 15 wt%) as a binder onto the first functional fiber layer to form a second adhesive fiber layer on the surface of the biopolymer nylon fabric. This second layer has an average fiber fineness of approximately 339 nm and a basis weight of approximately 4.95 g / m². 2 The basis weight; then another marine waste Nylon fabric is applied to the second adhesive fiber layer, and then the multilayer structure is hot-pressed by a hot press at a hot press roller speed of about 2 m / min and a hot press temperature of about 90°C to obtain the electrospun composite film of Example 5.
[0104] Further performance tests were conducted on the electrospun composite membrane of Example 5, including water pressure resistance, air permeability, moisture permeability, peel strength, rain test, and wash resistance test. The results showed that the electrospun composite membrane of Example 5 had a water pressure resistance of approximately 6,000 mmH2O, an air permeability of approximately 2 CFM, and a strength of approximately 60,000 g / m³. 2 *24hr moisture permeability, approximately 261g / cm peel strength, and has passed rain test (the weight difference before and after the absorbent paper test is approximately 0.2g) and wash resistance test (visually no peeling after 50 washes).
[0105] Example 6
[0106] In Example 6, marine waste Nylon fabric is fixed to a conveying device, which drives a first electrospinning device controlled by a voltage of approximately 80 kV. The first electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 15 wt%) as an adhesive onto the marine waste Nylon fabric to form a first adhesive fiber layer on the surface of the marine waste Nylon fabric, which has an average fiber fineness of approximately 350 nm and a fiber density of approximately 6.3 g / M.2 The basis weight; the marine waste Nylon fabric having the first bonded fiber layer is then driven by a conveying device through a second electrospinning device with a voltage controlled at about 80kV. The second electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of about 7wt%) as a functional solution onto the first bonded fiber layer to form a first functional fiber layer on the surface of the first bonded fiber layer, which has an average fiber fineness of about 284nm and a weight of about 11g / M 2 The basis weight and average pore size of approximately 0.82 μm; the marine waste Nylon fabric having a first adhesive fiber layer and a first functional fiber layer is then driven by a conveying device through a hot drying oven and heated to a temperature of approximately 120°C, and then further passed through a third electrospinning device with a voltage controlled at approximately 80 kV. The third electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 15 wt%) as an adhesive onto the first functional fiber layer to form a second adhesive fiber layer on the surface of the marine waste Nylon fabric, which has an average fiber fineness of approximately 352 nm and approximately 6 g / M 2 The basis weight; then another marine waste Nylon fabric is applied to the second adhesive fiber layer, and then the multilayer structure is hot-pressed by a hot press at a hot press roller speed of about 1 m / min and a hot press temperature of about 150°C to obtain the electrospun composite film of Example 6.
[0107] Further performance tests were conducted on the electrospun composite membrane of Example 6, including water pressure resistance, air permeability, moisture permeability, peel strength, rain resistance, and wash resistance. The results showed that the electrospun composite membrane of Example 6 had a water pressure resistance of approximately 8,000 mmH2O, an air permeability of approximately 1.4 CFM, and a strength of approximately 50,000 g / m³. 2 *24hr moisture permeability, approximately 277g / cm peel strength, and has passed rain test (the weight difference before and after the absorbent paper test is approximately 0.2g) and wash resistance test (visually no peeling after 50 washes).
[0108] Example 7
[0109] In Example 7, marine waste Nylon fabric is fixed to a conveying device, which drives a first electrospinning device controlled by a voltage of approximately 80 kV. The first electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 20 wt%) as an adhesive onto the marine waste Nylon fabric to form a first adhesive fiber layer on the surface of the marine waste Nylon fabric, which has an average fiber fineness of approximately 550 nm and a fiber density of approximately 7.7 g / M. 2The basis weight; the marine waste natron fabric having the first bonded fiber layer is then driven by a conveying device through a second electrospinning device with a voltage controlled at about 80kV. The second electrospinning device sprays an ethanol solution containing bio-natron (concentration of about 15wt%) as a functional solution onto the first bonded fiber layer to form a first functional fiber layer on the surface of the first bonded fiber layer, which has an average fiber fineness of about 261nm and a weight of about 10g / M 2 The basis weight and average pore size of approximately 0.78 μm; the marine waste Nylon fabric having a first adhesive fiber layer and a first functional fiber layer is then driven by a conveying device through a hot drying oven and heated to a temperature of approximately 130°C, and then further passed through a third electrospinning device with a voltage controlled at approximately 80 kV. The third electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 20 wt%) as an adhesive onto the first functional fiber layer to form a second adhesive fiber layer on the surface of the marine waste Nylon fabric, which has an average fiber fineness of approximately 526 nm and approximately 8.2 g / M 2 The basis weight; then another marine waste Nylon fabric is applied to the second adhesive fiber layer, and the multilayer structure is hot-pressed by a hot press at a hot press roller speed of about 0.5 m / min and a hot press temperature of about 150°C to obtain the electrospun composite film of Example 7.
[0110] Further performance tests were conducted on the electrospun composite membrane of Example 7, including water pressure resistance, air permeability, moisture permeability, peel strength, rain test, and wash resistance test. The results showed that the electrospun composite membrane of Example 7 had a water pressure resistance of approximately 9,000 mmH2O, an air permeability of approximately 0.8 CFM, and a strength of approximately 20,000 g / m³. 2 *24hr moisture permeability, approximately 276g / cm peel strength, and has passed rain test (the weight difference before and after the absorbent paper test is approximately 0.2g) and wash resistance test (visually no peeling after 50 washes).
[0111] Example 8
[0112] In Example 8, marine waste Nylon fabric is fixed to a conveying device, which drives a first electrospinning device controlled by a voltage of approximately 120 kV. The first electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 20 wt%) as an adhesive onto the marine waste Nylon fabric to form a first adhesive fiber layer on the surface of the marine waste Nylon fabric, which has an average fiber fineness of approximately 700 nm and a fiber density of approximately 10 g / m³. 2The basis weight; the marine waste natron fabric having the first bonded fiber layer is then driven by a conveying device through a second electrospinning device with a voltage controlled at about 120kV. The second electrospinning device sprays an ethanol solution containing bio-natron (concentration of about 15wt%) as a functional solution onto the first bonded fiber layer to form a first functional fiber layer on the surface of the first bonded fiber layer, which has an average fiber fineness of about 250nm and a weight of about 20g / M 2 The basis weight and average pore size of approximately 0.5 μm; the marine waste Nylon fabric having a first adhesive fiber layer and a first functional fiber layer is then driven by a conveying device through a hot drying oven and heated to a temperature of approximately 150°C, and then further passed through a third electrospinning device with a voltage controlled at approximately 120 kV. The third electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 20 wt%) as an adhesive onto the first functional fiber layer to form a second adhesive fiber layer on the surface of the Nylon weft elastic plain weave fabric, which has an average fiber fineness of approximately 538 nm and approximately 10 g / M 2 The basis weight; then another marine waste Nylon fabric is applied to the second adhesive fiber layer, and the multilayer structure is hot-pressed by a hot press at a hot press roller speed of about 0.5 m / min and a hot press temperature of about 150°C to obtain the electrospun composite film of Example 8.
[0113] Further performance tests were conducted on the electrospun composite membrane of Example 8, including water pressure resistance, air permeability, moisture permeability, peel strength, rain test, and wash resistance test. The results showed that the electrospun composite membrane of Example 8 had a water pressure resistance of approximately 20,000 mmH2O, an air permeability of approximately 0.3 CFM, and a strength of approximately 8,000 g / m³. 2 *24hr moisture permeability, approximately 294g / cm peel strength, and has passed rain test (the weight difference before and after the absorbent paper test is approximately 0.2g) and wash resistance test (visually no peeling after 50 washes).
[0114] Example 9
[0115] In Example 9, Nylon fabric is fixed to a conveying device, which drives a first electrospinning device controlled by a voltage of approximately 80 kV. The first electrospinning device sprays Nylon 6 as an adhesive onto the Nylon fabric to form a first adhesive fiber layer on the surface of the Nylon fabric, which has an average fiber fineness of approximately 213 nm and a fiber density of approximately 2.8 g / m³. 2 The basis weight; the Nylon fabric having the first bonded fiber layer is then driven by a conveying device through a second electrospinning device with a voltage controlled at approximately 90 kV. The second electrospinning device sprays Nylon 6 as a functional solution onto the first bonded fiber layer to form a first functional fiber layer on the surface of the first bonded fiber layer, which has an average fiber fineness of approximately 216 nm and a basis weight of approximately 4 g / m³. 2The basis weight and average pore size of approximately 0.8 μm; the Nylon fabric having a first adhesive fiber layer and a first functional fiber layer is then driven by a conveying device through a hot drying oven, heated to a temperature of approximately 200°C, and then passed through a third electrospinning device with a voltage controlled at approximately 90 kV. The third electrospinning device sprays Nylon 6 as an adhesive onto the first functional fiber layer to form a second adhesive fiber layer on the surface of the Nylon fabric, which has an average fiber fineness of approximately 200 nm and approximately 2.5 g / m³. 2 The basis weight; then another Nylon fabric is applied to the second adhesive fiber layer, and the multilayer structure is hot-pressed by a hot press at a hot press roller speed of about 1 m / min and a hot press temperature of about 260°C to obtain the electrospun composite film of Example 9.
[0116] Further performance tests were conducted on the electrospun composite membrane of Example 9, including water pressure resistance, air permeability, moisture permeability, peel strength, rain test, and wash resistance test. The results showed that the electrospun composite membrane of Example 9 had a water pressure resistance of approximately 2,000 mmH2O, an air permeability of approximately 8.2 CFM, and a strength of approximately 110,000 g / m³. 2 *24hr moisture permeability, approximately 204g / cm peel strength, and has passed rain test (the weight difference before and after the absorbent paper test is approximately 0.1g) and wash resistance test (visually no peeling after 50 washes).
[0117] Example 10
[0118] In Example 10, marine waste Nylon fabric is fixed to a conveying device, which drives a first electrospinning device controlled by a voltage of approximately 80 kV. The first electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 15 wt%) as an adhesive onto the marine waste Nylon fabric to form a first adhesive fiber layer on the surface of the marine waste Nylon fabric, which has an average fiber fineness of approximately 355 nm and a fiber density of approximately 15 g / m³. 2 The basis weight; the marine waste Nylon fabric having the first bonded fiber layer is then driven by a conveying device through a second electrospinning device with a voltage controlled at about 80kV. The second electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of about 7wt%) as a functional solution onto the first bonded fiber layer to form a first functional fiber layer on the surface of the first bonded fiber layer, which has an average fiber fineness of about 278nm and a weight of about 11g / M 2The basis weight and average pore size of approximately 0.81 μm; the marine waste Nylon fabric having a first adhesive fiber layer and a first functional fiber layer is then driven by a conveying device through a hot drying oven and heated to a temperature of approximately 120°C, and then further passed through a third electrospinning device with a voltage controlled at approximately 80 kV. The third electrospinning device sprays an ethanol solution containing bio-Nylon (concentration of approximately 15 wt%) as an adhesive onto the first functional fiber layer to form a second adhesive fiber layer on the surface of the Nylon weft elastic plain weave fabric, which has an average fiber fineness of approximately 343 nm and approximately 15 g / M 2 The basis weight; then another marine waste Nylon fabric is applied to the second adhesive fiber layer, and the multilayer structure is hot-pressed by a hot press at a hot press roller speed of about 1 m / min and a hot press temperature of about 110°C to obtain the electrospun composite film of Example 10.
[0119] Further performance tests were conducted on the electrospun composite membrane of Example 10, including water pressure resistance, air permeability, moisture permeability, peel strength, rain test, and wash resistance test. The results showed that the electrospun composite membrane of Example 10 had a water pressure resistance of approximately 8,000 mmH2O, an air permeability of approximately 1.0 CFM, and a strength of approximately 49,000 g / m³. 2 *24hr moisture permeability, approximately 312g / cm peel strength, and has passed rain test (the weight difference before and after the absorbent paper test is approximately 0.2g) and wash resistance test (visually no peeling after 50 washes).
[0120] The electrospun composite membrane obtained by the method or system disclosed herein has improved breathability (>0.3 CFM) because both the adhesive fiber layer and the functional fiber layer use electrospinning technology. This helps to promote airflow through the electrospun composite membrane, avoids stuffiness, and improves wearing comfort. In contrast, currently commercially available composite membranes cannot achieve such high breathability.
[0121] Furthermore, the electrospun composite membrane obtained by the method or system disclosed herein also exhibits high moisture permeability (≥8,000 g / m³). 2 *24hr) It can quickly wick away sweat and moisture to keep you dry, making it especially suitable for high-intensity outdoor activities. Even though both the adhesive fiber layer and the functional fiber layer have an average fiber fineness of several nanometers, they still achieve a water pressure resistance of ≥10,000 mmH2O and have passed rain tests, thus providing excellent waterproof performance and effectively blocking the penetration of moderate to heavy rain, making them suitable for extreme weather conditions.
[0122] The foregoing has provided a fairly comprehensive overview of the technical features and advantages of this disclosure, enabling a good understanding of it. Those skilled in the art will understand that the concepts and specific embodiments disclosed above can be readily utilized to modify or design other structures or processes to achieve the same objectives as disclosed herein. Those skilled in the art will also understand that such equivalent structures and methods remain within the spirit and scope of this disclosure as defined in the claims.
[0123] [Symbol Explanation]
[0124] 10 Conveying device
[0125] 11 Input Terminal
[0126] 12 Output terminals
[0127] 13 Support rollers
[0128] 20 First electrospinning device
[0129] 21 Adhesive Receptacle Components
[0130] 22 Spray nozzle
[0131] 30 Second electrospinning apparatus
[0132] 31 Functional solution containment components
[0133] 32 spray nozzles
[0134] 40°C Hot Drying Oven
[0135] 41. Hot air drying oven rollers
[0136] 50 Third electrospinning device
[0137] 51 Adhesive Receptacle Component
[0138] 52 Spray nozzle
[0139] 60 Fabric feeding device
[0140] 70 Hot Press
[0141] 71 Hot Press Roller
[0142] 90 Electrospun Composite Film
[0143] 91 First base cloth
[0144] 92 First adhesive fiber layer
[0145] 93 First functional fiber layer
[0146] 94 Second adhesive fiber layer
[0147] 95 Second base fabric.
Claims
1. A method for preparing an electrospun composite film, comprising: The first base fabric is fixed to the conveying device; The first base fabric is driven by the conveying device and passed through the first electrospinning device to form a first adhesive fiber layer on a surface of the first base fabric; The first base fabric having the first adhesive fiber layer is driven by the conveying device and passed through the second electrospinning device to form a first functional fiber layer on the first adhesive fiber layer of the first base fabric; and The first base fabric having the first adhesive fiber layer and the first functional fiber layer is driven by the conveying device and passed through a hot press to form the electrospun composite film.
2. The method for preparing the electrospun composite film as described in claim 1, wherein before the first base fabric having the first adhesive fiber layer and the first functional fiber layer passes through a hot press, the preparation method further comprises: The first base fabric having the first adhesive fiber layer and the first functional fiber layer is driven by the conveying device and passed through a hot drying oven; A first base fabric having the first adhesive fiber layer and the first functional fiber layer is driven by the conveying device and passed through a third electrospinning device to form a second adhesive fiber layer on the first functional fiber layer; and The second base fabric is applied to the second adhesive fiber layer and passed through the hot press to form the electrospun composite film.
3. The method for preparing the electrospun composite film as described in claim 2, wherein the temperature of the hot drying oven is higher than the melting point of the material of the first adhesive fiber layer and lower than the melting point of the material of the first functional fiber layer.
4. The method for preparing the electrospun composite film according to any one of claims 1 to 3, wherein the temperature of the hot press is higher than the melting point of the material of the first adhesive fiber layer and lower than the melting point of the material of the first functional fiber layer.
5. The method for preparing an electrospun composite membrane according to any one of claims 1 to 3, wherein the first electrospinning device, the second electrospinning device and the third electrospinning device are needleless electrospinning devices.
6. The method for preparing an electrospun composite membrane according to any one of claims 1 to 3, wherein the average fiber fineness of each of the first adhesive fiber layer and the second adhesive fiber layer is equal to or greater than the average fiber fineness of the first functional fiber layer; and the basis weight of each of the first adhesive fiber layer and the second adhesive fiber layer is equal to or less than the basis weight of the first functional fiber layer.
7. The method for preparing the electrospun composite film according to any one of claims 1 to 3, wherein the first functional fiber layer comprises one or more additives selected from water-repellent agent, antibacterial agent, deodorant, anti-mite agent or colorant.
8. A system for preparing an electrospun composite membrane, comprising: A conveying device, comprising an input end and an output end; A first electrospinning device is disposed between the input end and the output end of the conveying device, and includes an adhesive receiving component. A second electrospinning device, disposed between the output end of the first electrospinning device and the conveying device, includes a functional solution-containing component; and A hot press is disposed between the output end of the second electrospinning device and the conveying device.
9. The system for preparing an electrospun composite membrane as described in claim 8, further comprising: A hot drying oven is disposed between the second electrospinning device and the hot press; The third electrospinning device is located between the hot drying oven and the hot press. and A fabric input device is disposed between the third electrospinning device and the hot press.
10. The system for preparing electrospun composite films as described in claim 9, wherein the temperature of the hot oven is from 60°C to 200°C.
11. The system for preparing an electrospun composite film according to any one of claims 8 to 10, wherein the hot pressing temperature of the hot press is from 80°C to 300°C.
12. The system for preparing an electrospun composite membrane as claimed in any one of claims 8 to 10, wherein the first electrospinning device, the second electrospinning device and the third electrospinning device are needleless electrospinning devices.
13. The system for preparing an electrospun composite membrane according to any one of claims 8 to 10, wherein each of the first adhesive fiber layer and the second adhesive fiber layer has an average fiber fineness of 200 nm to 700 nm and a weight per square meter (g / M). 2 Up to 20g / M 2 The basis weight; the first functional fiber layer has an average fiber fineness of 80 nm to 500 nm and 1 g / M 2 Up to 20g / M 2 The base weight.
Citation Information
Patent Citations
Needle-free electrostatic spinning polymer nanofiber large-scale quick continuous manufacturing system
CN104532482A
Breathable and waterproof cloth and manufacturing method thereof
TW202428958A